Interpreting construction contracts fundamental principles for contractors, project managers, and contract administrators - Thomas, H. Randolph, 1945- (American Society of Civil Engineers, 2007)
"In Interpreting Construction Contracts, Thomas and Ellis seek to rescue contractors, project managers, and contract administrators struggling to interpret these contracts. By using rules set forth by the judiciary and drawing upon decades of legal research and practical experience, the authors discuss the most troublesome contract clauses and present rules to construe them so as to avoid disputes that must be resolved in court. Diagrams and case studies appear, as well as over 70 discussion exercises and solutions, reinforcing the principles introduced in each chapter."--BOOK JACKET.
Keywords: Construction contracts -- United States.; Construction contracts -- United States -- Interpretation and construction.; Contractors -- United States -- Handbooks, manuals, etc.; Project managers -- United States -- Handbooks, manuals, etc.; elektronické knihy; electronic books